2011
DOI: 10.1182/blood.v118.21.5204.5204
|View full text |Cite
|
Sign up to set email alerts
|

Role of FDG-PET/CT in Detecting Lymphomatous Bone Marrow Involvement in Patients with Newly Diagnosed Diffuse Large B-Cell Lymphoma

Abstract: 5204 Backgrounds: As a bone marrow bopsy (BMB) is a painful and invasive procedure with a restrictive reliability as only a limited area of the bone marrow (BM) can be evaluated, role of FDG-PET/CT to demonstrate lymphomatous BM involvement as an alternative or at least a complementary to BMB is an area of interest. Several previous studies exist but most of them included heterogeneous types of lymphomas with various treatments. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Our findings support those of a recent meta-analysis of seven studies, which demonstrated a pooled sensitivity and specificity of FDG PET/CT of 88.7% and 99.8%, respectively, in newly diagnosed DLBCL (6). Individual studies have found sensitivity of PET/CT in this setting of 70.7–95.8%, with specificity of 99.0–100% (Table 5) (4,1317).…”
Section: Discussionmentioning
confidence: 99%
“…Our findings support those of a recent meta-analysis of seven studies, which demonstrated a pooled sensitivity and specificity of FDG PET/CT of 88.7% and 99.8%, respectively, in newly diagnosed DLBCL (6). Individual studies have found sensitivity of PET/CT in this setting of 70.7–95.8%, with specificity of 99.0–100% (Table 5) (4,1317).…”
Section: Discussionmentioning
confidence: 99%
“…In the setting of B-NHL, and particularly in the DLBCL category, the use of PET/CT and/or BMB for staging purposes is presently one of the most debated issues as different strategies have been proposed according to the divergent results of a number of distinct series or metaanalysis [3][4][5][6][7][8][12][13][14][15], or experience-based recommendations from experts in the field [4,5,[16][17][18][19][20]. With an endeavor to avoid susceptibility and collinearity biases in our study design, we show here the superiority of BMB over PET/CT in predicting PFS in a homogeneously-treated cohort of 203 DLBCL patients.…”
Section: Discussionmentioning
confidence: 99%
“…The fact that a negative end-of-treatment FDG-PET fails to predict a favourable outcome in a non-negligible proportion of patients is due to its inherent limitations. First, despite the fact that DLBCL is FDG-avid in the vast majority of cases (Weiler-Sagie et al, 2010) and FDG-PET is thus considered a sensitive staging method in this disease Cheson et al, 2014), recent studies have indicated that FDG-PET is insufficiently accurate for the detection of bone marrow involvement (Hong et al, 2012;Hong & Lee, 2013;Adams et al, 2014a,b). This, in turn, suggests that FDG-PET is not a suitable method to confirm bone marrow remission status.…”
Section: Discussionmentioning
confidence: 99%